IMPACT OF MENTAL HEALTH FOR CHILDREN AND ADOLESCENTS DURING PANDEMIC: LITERATURE REVIEW - Rahma Fadila, Syasa; Muzdhalifa Maulana , Intan; Apriningsih, Apriningsih (Jurnal Kesehatan Langkat Berseri (JURKESLASER), 2021)
Covid-19 Pandemic struck Indonesia back in 2020 that makes Indonesia tighten its alertness to society in Covid-19 infection. Government policies such as large-scale social distancing (PSBB), restriction on community activities (PPKM) that affected several sectors, including health, social, economy, and education, even affect children and teenager mental health. The goal of this research is to know the mental health impact on children and adolescents during Covid-19 Pandemic. This research is using literature review method and electronic databases such as Google Scholar, Springer, PubMed using relevant keywords such as Pandemic, Mental Health, Children & Adolescents. The chosen articles are from 2019 – 2021, up to 11 articles. This research emphasizes recent articles, using cross-sectional method. In this research, it was found that the effects of mental health during pandemic towards children and teenager are anxiety, depression, social distance, social isolation, eating disorder, lack of parental attention, lack of parent’s economy, and domestic abuse.